Pendidikan Karakter dalam Komik Si Toyeb Karya Husni Assaerozi - Hayati Wahyuni, Hayati; Bahanan, Mochamad Abduloh (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2021)
In constitution Number 20 of 2003 year Chapter 2 Article 3 talking about the national education system said that "national education aims to develop the ability and form the character and civilization nation that dignity in order to educate life of the nation, aiming to develop the potential of students become human beings who faithful and pious to God Almighty, noble, healthy, erudite, capable, creative, independent, and become democratic and responsible citizen.  The values of character education should be instilled in children since early age. This is duty of both parents to educate their children to have good behaviors and habits. Whether at home, at school or in the society circle. The comic book entitled Si Toyeb by Husni Assaerozi. This research aims to trace the characters education in the comic Si Toyeb which is a comic that tells about the portrait of santri life in Islamic boarding school. This written is a research that seeks to inspect the values of character education using library research methods. Data from the results of this research can be concluded that comic Si Toyeb by Husni Assaerozi there are 9 from 18 characters education values according national education ministry.